Geometric Optimization of Coanda Jet Chamber Fins via Response Surface Methodology - Hui Zhang; Kai Yue; Yiming Zhang (Aerospace)
A highly loaded axial flow compressor often leads to significant flow separation, resulting in increased pressure loss and deterioration of the pressure increase ability. Improving flow separation within a compressor is crucial for enhancing aeroengine performance. This study proposes adding a fin structure to the jet cavity of the Coanda jet cascade to improve flow separation at the trailing edge and corner area. The fin structure is optimized using response surface technique and a multi-objective genetic algorithm based on numerical simulation, enabling more effective control of the simultaneous separation of the boundary corner and trailing edge of the layer. The response surface model developed in this study is accurately validated. The numerical results demonstrate a 2.13% reduction in the optimized blade total pressure loss coefficient and a 12.74% reduction in the endwall loss coefficient compared to those of the original unfinned construction under the same air injection conditions. The optimization procedure markedly improves flow separation in the compressor, leading to a considerable decrease in the volume of low-energy fluid on the blade’s suction surface, particularly in the corner area. The aerodynamic performance of the high-load cascade is enhanced.